Association of Knee Pain and Crouch Gait in Individuals With Cerebral Palsy. Issue 6 (July 2020) - Pelrine, Eliza; Novacheck, Tom; Boyer, Elizabeth
Abstract : Background: Crouch gait (ie, excessive knee flexion) is commonly seen in patients with cerebral palsy (CP) and has been inconsistently linked with knee pain. The definitive cause of knee pain is unknown, but may result from increased joint forces due to crouch gait kinematics. Our purpose was to determine whether knee pain is positively associated with knee flexion in gait among a large sample of ambulatory individuals with CP. We hypothesized that knee pain prevalence would increase as knee flexion increased. Methods: In this retrospective study, pain questionnaire and 3-dimensional gait analysis data from 2015 to 2018 were extracted from the medical records of individuals with CP who had a clinical gait analysis. The pain questionnaire asked caregivers/patients to indicate the location of pain and when it occurs. A multivariate logistic regression was performed with minimum knee flexion in stance, patella alta, age, and sex as predictors of knee pain. Results: Among the 729 participants included in the analysis, 147 reported knee pain (20.1%). The odds of knee pain were not associated with minimum knee flexion in stance or sex. However, the odds of knee pain increased 73.2% when patella alta was present ( P =0.008) and tended to increase 2.2% as age increased ( P =0.059). Conclusions: The data suggest that there is not a meaningful association between crouch gait and knee pain. Having patella alta was associated with pain. Further studies that use validated pain questionnaires are needed to understand the multifactorial etiology of knee pain within ambulatory individuals with CP. Level of Evidence: Level III—case-control study.